Extrastriate visual cortex in idiopathic occipital epilepsies: The contribution of retinotopic areas to spike generation. (19th April 2016) - Meletti, Stefano; Ruggieri, Andrea; Avanzini, Pietro; Caramaschi, Elisa; Filippini, Melissa; Bergonzini, Patrizia; Monti, Giulia; Vignoli, Aglaia; Olivotto, Sara; Mastrangelo, Massimo; Santucci, Margherita; Gobbi, Giuseppe; et al.
Summary: Objectives: To provide insight into the pathophysiology of idiopathic childhood occipital epilepsies (ICOEs), by mapping the contribution of retinotopic visual areas to the generation and sustainment of epileptic activity. Methods: Thirteen patients affected by ICOEs (mean age = 10.9 years) underwent a video electroencephalography–functional magnetic resonance imaging (EEG‐fMRI) study. A flexible‐related fMRI analysis was applied to estimate the shape of the blood oxygen level–dependent (BOLD) response in each patient. Second‐level analysis was performed using the interictal EEG discharge (IED)–specific response shape for the ICOE group. The resulting fMRI t‐maps were warped to the Population‐Average, Landmark‐ and Surface‐based (PALS)‐B12 atlas in Caret. For localization purposes, functional results were plotted and compared against 19 retinotopic areas for each hemisphere. A correlation analysis was performed between the hemodynamic maps and electroclinical variables. Results: The shape of the group‐averaged hemodynamic response in ICOE patients showed an earlier time‐to‐peak and a more pronounced undershoot than the canonical hemodynamic response function (HRF). The random‐effect analysis showed positive hemodynamic changes in the bilateral temporooccipital network. With regard to the retinotopic subdivision of the visual cortex, the primary visual area was consistently spared. Conversely, an extensive involvement of the occipitotemporal cortex, including the fusiform gyrus, and the occipitoparietal areas was observed. Moreover, a linear relationship was detected between the occipital spike‐density and BOLD increases at the postcentral gyrus and temporooccipital cortex. Significance: Our data indicate that both the ventral and dorsal visual pathways are involved in spike generation in ICOEs, to extents that vary between patients, and reinforce the concept of benign childhood seizure susceptibility syndrome as a substrate for ICOEs. Finally, these results underscore the need for appropriate neuropsychological testing in these children, aimed at revealing selective impairments in functions subserved by both visual pathways.